Optimización de portafolios de pensiones en Colombia: el esquema de multifondos, 2003-2010 (2020)
The aim of this research is to find out an optimal composition of a portafolio investment, according with the conditions proposed in the new Colombian retirement pension system (Multifondos), during June 2003-September 2010. Calculations were done using Markowitz´s efficient portafolio model. It was found that foreign investment might means low returns compared with those made in local market because of the actual local currency revaluation. Furthermore, the results obtained through the efficient frontier calculus show that those points with regard to “la ley 100”, “Fondo conservador, “Fondo moderado”, and “Fondo agresivo” are below the frontier what it means that Multifondos returns are not the best despite of all the modifications made in the Law 1328. Last but not least, the FPO should take into account all policies recommendations made by the OCDE, specially those regarding strategical and tactical asset assignation, due to the absurd results found in this research.